ISLAM NUSANTARA AND ISLAM ADVANCE IN THE PERSPECTIVE OF NAHDLATUL ULAMA AND MUHAMMADIYAH - Yuliansyah, Yuliansyah (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
This research discusses Nahdatul Ulama (NU) and Muhammadiyah are two very popular proselytizing organizations in Indonesia. NU which is known for its tolerance to traditions in Indonesia and Muhammadiyah which is known as Islamic purification and its breakthrough in the world of education. Both have different characteristics, although basically want to introduce Islam and its teachings to everyone. Both also have a large number of members, often looking different directions and different policies. But both still make the Qur'an and hadith their foundation. The focus of this study is how Islam is archipelago, and Islam advances according to the perspective of Nu and Muhammadiyah?. The method used in this research is a type of literature research with a historical approach. The result of this research is that Islam Nusantara also places the pribumization of Islam as a methodology for the formulation of Islam Nusantara as well as nu Islam's proselytizing method of advancing not thinking in an ivory tower, but has been grounded for more than a century by Muhammadiyah in various best-practices through modern institutions Including through charitable efforts in various superior fields such as education, health, social, empowerment, economy, and community proselytizing that bring about the betterment of the wider community